An evaluation of a digital pain management programme: clinical effectiveness and cost savings. Issue 4 (November 2020) - Pimm, Theo John; Williams, Laura Juliette; Reay, Megan; Pickering, Stephen; Lota, Ranjeeta; Coote, Laura; Maloney, Ciara; Hancock, David; Sarhan, Firas
Introduction: Chronic pain is one of the most prevalent causes of disability worldwide, and digital interventions may be one of the ways to meet this need. Randomised controlled trials have demonstrated that digital interventions can be effective in treating chronic pain. This study aimed to establish the clinical effectiveness of a web-based pain management programme (PMP), specifically whether it would lead to improved clinical outcomes and reduced health care costs in a real-world clinical setting. Methods: Of 738 participants, 438 engaged with the programme and 300 did not. Two analyses were conducted: a within-subjects pre–post comparison of clinical outcomes for participants who completed the programme and a between-groups comparison of health care usage for those who engaged and those who did not. Results: Participants who completed the programme made significant improvements with regard to their perceived health status, level of disability, mood, confidence managing pain, problems in life due to pain and level of pain. Around one-third of participants made reliable changes in their levels of disability, depression and anxiety. There was no relationship between gender or age and engagement with the programme. Those who engaged with the programme demonstrated reduced health care costs in the year following referral, whereas health care costs of non-engagers increased. Limitations of the study include a high drop-out rate and a non-randomised comparison group. Results must therefore be interpreted with some caution. Conclusion: A web-based pain management programme can be clinically effective and may be a useful addition to the treatments offered by pain management services.